(untitled) (Journal of Forest and Livelihood, 2017)
Nepal’s Leasehold Forestry (LHF) programme,which has the twin goals of degraded forest rehabilitation and rural poverty alleviation, started in the early 1990s and is regarded as a priority forestry programme in Nepal.There has been limited documentationof the impact of the LHF programme as well as of the issues and challenges faced by it. On the basis of scarce existing literature and of our long experience working in the programme, we, in this paper, discuss such impacts, issues and challenges. We suggest that the programme has so far been quite positive in meeting the stated objectives; however, there remains a range of issues that deserve on-going attention. While the programme, in general, is criticized for its strategy of handing over poor quality land to the poor people, the communities’ tenure rights over land and forest resources is not fully secured either. Provisions regarding the transfer of tenure rights to the kin and/or in the context of absentees are absent, and the benefit sharing mechanisms are unclear in case of trees which were present at the time of handover, and compete across other overlapping forest management activities. Support services available to the LHF user groups are inadequate and discontinuous, limiting the opportunities for the poor leaseholders to harness their potential to pool resources from other poverty reduction programmes and influence policy processes. We indicate some areas of intervention at policy and programme levels that seek to overcome these issues and to provide wider space for LHF user groups to exercise their agency towards achieving the programme’s goals effectively, efficiently and equitably.